Energy Storage Ratio in Off-Grid Renewable Energy Hydrogen Production System - Hang ZHOU; Hui WANG; Xinrui LI; Shaohua LI; Jing FENG; Xiaoshu TANG; Jun ZHOU (南方能源建设)
[Objective] Off-grid new energy hydrogen production projects not only have significant emission reduction effects, but also serve as industrial demonstrations and driving forces. Off-grid power systems and their applications in the field of hydrogen production are still in their infancy. In the project design stage, the capacity ratio of energy storage devices will directly affect the overall stability and hydrogen production cost of off-grid hydrogen production systems. At present, there is no specification to clearly specify the energy storage ratio. [Method] Based on the summary and analysis of traditional grid-connected power systems, the stability conditions of off-grid hydrogen production systems primarily powered by new energy were proposed. In this study, an off-grid hydrogen production system with electrolyzer as the main load was established on the ETAP simulation platform. The simulation included three typical simulation conditions and energy storage ratios of 10%, 20%, 30% and 40%, and the system stability was compared and analyzed. [Results] The simulation results show that for the off-grid hydrogen production system constructed in this paper, it is necessary to configure energy storage components with at least 20% of the installed capacity of new energy to mitigate the fluctuations caused by the regulation of the system power supply or load end, and to ensure the stability of voltage and frequency in subsequent operation of the system. [Conclusion] More than 20% energy storage configuration can ensure that the system voltage fluctuation is less than 3% and the frequency fluctuation is within ±0.5Hz after system regulation or fault elimination. A higher energy storage ratio can effectively dampen the peak fluctuations in the system voltage or frequency, so that the system can recover faster, but there is no regulation to limit this, and it also depends on the overload multiples allowed by system components other than energy storage components.